Incorporating silica synthesized from rice husk ash into a calcium oxide catalyst for biodiesel production - Alhanif, Misbahudin; Mustafa, Mustafa; Kumoro, Andri Cahyo; Wahyono, Yoyon; Zaim, Hanif Fawwaz; Zahra, Nurul Afifah (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2025)
Biodiesel represents a promising renewable energy alternative to either substitute or be blended with conventional diesel, offering advantages such as a high cetane number, reduced sulfur (SOx) and CO₂ emissions, and greater environmental sustainability. The application of calcium oxide (CaO) as a basic catalyst in biodiesel production has been extensively reported. However, its catalytic performance is limited by its sensitivity to moisture, which can negatively affect the reaction rate. In addition, some of the Ca2+ ions in the catalyst can dissolve in the mixture of biodiesel and glycerol, causing product contamination. This study aims to combine a CaO catalyst from marble powder with sulfonated silica (SiO2) from rice husk ash (RHA) to enhance the distribution of catalyst particles, reduce crystallinity, and increase the surface area of the catalyst. This study was conducted through chemical and thermal activation of SiO2 from RHA, sulfonation of SiO2, thermal activation of CaO from marble powder waste, and impregnation of CaO/SiO2 catalyst with variations in CaO/SiO2 composition (25%:75%, 50%:50%, 75%:25%). The results showed that the purity of SiO2 and CaO obtained through chemical and thermal activation was 93.67% and 99.13%, respectively. The sulfonation process on SiO2 successfully added –SO3 groups at 36.5%, which supported the formation of acid sites on the catalyst. Characterization showed that the surface morphology was composed of particles measuring 2–8 µm with a dominant amorphous structure. The addition of SiO2 gave rise to new crystal peaks but decreased the crystal intensity, especially at the 50%:50% composition. The composition of CaO/SiO2 at 75%:25% showed the best physical properties with a surface area of 22.24 m²/g, a pore volume of 65.29 mm³/g, and a pore diameter of 11.74 nm, indicating high potential as a bifunctional catalyst for biodiesel esterification–transesterification.